ANALISIS PENGETAHUAN DAN PENANGGULANGAN DISMINORHEA PADA SISWI SEBELUM DAN SESUDAH PENERAPAN LEAFLET DAN LEMBAR BALIK - Sri Susanti; Ika Apriyanti; Lina Marliana (Journal Of Applied Health Research And Development, 2020)
Menstruation as vaginal bleeding that occurs periodically due to the release of the uterine mucosa. The menstrual cycle begins with menarche and will continue until menopause around the age of 45-55 years. Studies of systematic reviews in developing countries find that 25-50% of adult women and around 75% of adolescents experience painful sensations during menstruation, with five to twenty percent reported experiencing dysmenorrhea severeor inhibiting them in their daily activities. This study aims to try to give treatment to a counseling model by using leaflet and flipchart media then analyze the level of change before and after the model is applied and the results of this study are expected to be used as a reference for health, dysmenorrhea especially for students who are still called the juvenile category to improve coping patterns when menstruation is coming The research method used was to use a survey method, which is a research design that provides both quantitative and numerical descriptions. Sampling using purposive random sampling of 420 students. The results of the study were analyzed in stages through univariate and bivariate analysis. The results showed that the average value of knowledge change using flip media (77.98) was greater than the media leaflet (77.48). The results of the analysis of the method leaflet and flipchart with the Wilcoxon Test obtained p-value = 0,000, which means that both media influence increasing knowledge about dysmenorrhea students. It was concluded that the method leaflet and the flipchart method both had effects on the score of student knowledge about menstrual pain (dysmenorrhea)